KREASI LILIN DARI LIMBAH JELANTAH: PELATIHAN WIRAUSAHA HIJAU BERBASIS EKONOMI KREATIF DI RA PERMATA PISANGAN CIPUTAT TANGERANG SELATAN - Sufyati HS; Tati Handayani; Subur, Subur; Alfida Aziz; Anita Nopiyanti; Nurhafifah Matondang (LPSDI Bina Patria, 2025)
The Candle Creation from Used Cooking Oil Waste training program was conducted at RA Permata Pisangan, Ciputat, South Tangerang, with the aim of introducing the concept of green entrepreneurship based on creative economy to parents of students. The activity involved 20 parents who actively participated in the entire training process, including socialization, hands-on practice in processing used cooking oil, and the creation of environmentally friendly candles. The training aimed to raise awareness of household waste management and to encourage the development of creative business opportunities using materials previously considered as waste. The results indicated that the program successfully improved participants’ knowledge and skills in transforming used cooking oil into economically valuable products. Participants showed high enthusiasm through active engagement during the training and expressed interest in further developing candle products as a potential source of income. This program also inspired participants to implement circular economy principles within their households. Thus, the training contributed not only to environmental pollution reduction but also encouraged community participation in creating sustainable solutions through creative and entrepreneurial approaches